One-Pot Synthesis of Pyranocarbazoles by Ethylenediamine Diacetate Catalyzed Domino Aldol-Type Reaction/6π-Electrocyclization of Hydroxycarbazoles to α,β-Unsaturated Aldehydes and Conversion into Other Pyranocarbazoles - Pandit, Rameshwar Prasad; Lee, Yong Rok (Synthesis, 2012)
A new synthetic route for biologically interesting pyranocarbazoles was developed by reaction of 2- or 4-hydroxycarbazole with α,β-unsaturated aldehydes in the presence of ethylenediamine diacetate (EDDA). The key strategy of this methodology is a formal [3+3] cycloaddition via domino aldol-type/6π-electrocyclization. The synthesized pyranocarbazoles can be converted into derivatives bearing substituents on the carbazole and pyran rings.
Keywords: pyranocarbazoles; ethylenediamine diacetate; domino reaction; heterocycles; cyclization